LANDSCAPE DISTRIBUTION OF SURFACE VERTEBRATE ANIMALS AND NEW TASKS OF ANIMAL STUDY - Joldasbayeva, E.K. (SCIENCE and SOCIETY, 2026)
The article describes the natural-geographical location of the Republic of Karakalpakstan, the structure of the landscape and the territorial distribution of the animal world, the factors influencing the species, number, and distribution of the animal world, the emerging ecological problems, environmental degradation and their impact on the fauna of the region, the preservation of biodiversity, ensuring ecological sustainability, and the development of scientific research.